MODIFIKASI BRAKE SYSTEM MESIN BUBUT DOALL - Andre Rowanda; Aji Sultan; Husman; Rodika (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
The mechanical workshop laboratory of Bangka Belitung State Manufacturing Polytechnic has various machine tools, including a DoAll lathe that has been used for 29 years and has various damages, especially to the braking system. The damage to the braking system is caused by the age of the machine and the difficulty of obtaining original spare parts, resulting in constraints in maintenance and malfunction of the braking system. Braking is a crucial aspect in lathe operation to prevent work accidents and machine damage, and is important in practicum activities, especially in thread making. This research uses the experimental design method by modifying the braking system of the DoAll lathe using the braking system of a motor vehicle (motor/car) to facilitate the replacement of parts. The purpose of this final project is to modify the braking system of the DoAll lathe so that it can return to optimal operation. Based on the function test results, the braking system modification using the Daihatsu Taft F70 car braking system is proven to work well and is able to brake without damage.